Policing Johannesburg wealthy neighborhoods: the uncertain ‘partnerships’ between police, communities and private security companies - Benit Gbaffou, Claire (Trialog, 2006)
The paper examines the challenges raised by “partnerships” between state and non-state security stakeholders, relying on two security experiments developed in Johannesburg wealthy neighborhoods. It raises the question of their monitoring by the police – understood as the police capacity to coordinate the multiple, non-state policing initiatives that otherwise remain fragmented “security networks”. The community initiatives seem easier to integrate within the local police strategies – since the private security sector has got its own, marketdriven logic. However, the formalisation of partnerships between police and communities have generally failed, due to their technical fragility (flexibility of community involvement, personalization of relationships leading to possible corruption and conflict) and their political difficulties (if the private sector can easily target the high income area, it is considered less legitimate for police to set up “elitist policing” thanks to the involvement of wealthy communities). Finally, abandoning these forms of partnerships might encourage a further privatization of the production of security – using more classical, easier-to-set “contracts” with the private sector that do not seem to lead to a real “partnership” with, nor a monitoring by, the police.
Keywords: Partnerships state and non-state, non-state policing initiatives, fragmented security networks, community initiatives, partnerships police and communities.